ATTITUDES OF CZECH AND SLOVAK YOUNG PROFESSIONALS TOWARDS POTENTIAL NEW ENTRANTS IN THE AUTOMOTIVE INDUSTRY (Perner's Contacts, 2021)
The automotive industry is changing rapidly. Are these changes what the car customer prefers? This paper gives insights into attitudes towards new automotive brands, the brand image of big tech companies, perceptions regarding the cooperation between car manufacturers and tech companies, purchasing drivers of new brands, and willingness to pay for big tech brands in automotive. In-depth interviews with young professionals in the Czech Republic and Slovakia were conducted with the use of an interview guide.